1996
DOI: 10.1097/00003246-199605000-00003
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the safety and efficacy of the monoclonal anti-tumor necrosis factor antibody-fragment, MAK 195F, in patients with sepsis and septic shock

Abstract: There was no increase in survival from sepsis for the patients receiving anti-TNF treatment in the overall study population. Retrospective stratification of patients by IL-6 concentrations suggests beneficial effects of the drug for patients with baseline circulating IL-6 concentrations of > 1000 pg/mL. This hypothesis requires validation in a larger, blinded, prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0
11

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(126 citation statements)
references
References 38 publications
0
115
0
11
Order By: Relevance
“…Nevertheless, the heterogeneous and dynamic nature of sepsis requires an adequate risk stratification in terms of not only research, but also therapeutic strategies (49). For example, a phase II trial by Reinhart et al found beneficial effects of treatment with the anti-TNF antibody fragment MAK 195F only in septic patients with IL-6 blood levels above 1,000 pg/mL (50).…”
Section: Anti-inflammatory Therapies In Sepsis: a Hopeless Case?mentioning
confidence: 99%
“…Nevertheless, the heterogeneous and dynamic nature of sepsis requires an adequate risk stratification in terms of not only research, but also therapeutic strategies (49). For example, a phase II trial by Reinhart et al found beneficial effects of treatment with the anti-TNF antibody fragment MAK 195F only in septic patients with IL-6 blood levels above 1,000 pg/mL (50).…”
Section: Anti-inflammatory Therapies In Sepsis: a Hopeless Case?mentioning
confidence: 99%
“…The pathophysiologic relevance of such TNF ␣ -related mechanisms to tissue injury is supported by observations that inhibition of TNF ␣ processing to the active form, passive immunization with neutralizing anti-TNF ␣ antibodies, or gene deletion of the 55-kD TNF ␣ receptor increase survival in animal models of endotoxemia (16)(17)(18)(19)(20)(21)(22)(23). However, clinical studies using TNF ␣ -neutralizing antibodies in the treatment of sepsis failed to show clear physiological or survival benefits in the overall study population (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…This inflammatory cascade can become self-sustaining when cytokines produced early in the infectious process (e.g., tumor necrosis factor alpha [TNF-␣] and interleukin-1 [IL-1]) induce further production of these and other proinflammatory cytokines (20,44) Agents directed at common triggers for the sepsis syndrome (e.g., lipopolysaccharide [LPS]) or cytokines (e.g., TNF-␣ and IL-1) associated with systemic inflammation would, at least conceptually, be attractive therapeutic targets (1,14). Regrettably, most of these potentially novel therapeutic approaches have failed to significantly affect the overall mortality of sepsis patients despite their success in many experimental animal models of sepsis (1,2,9,16,29,38). One potential explanation for these repeated clinical failures is that sepsis, in fact, represents a heterogeneous collection of clinically related diseases whose pathogenesis may vary substantially, depending upon the microbe responsible for inducing the systemic proinflammatory cascade (e.g., gram-negative versus gram-positive organisms) (6,34,43).…”
mentioning
confidence: 99%